Responses of tidal dynamic and water exchange capacity to coastline change in the Bohai Sea, China - Wu, Zhengcheng; Zhou, Chunyan; Wang, Peng; Fei, Zihao (Frontiers in Marine Science, 2023)
Bohai Sea (BHS) is a semi-enclosed shallow continental sea in China that has suffered from the deteriorative hydrodynamic environment due to large-scale reclamation. Single-factor simulations of tidal dynamic and material transport under the influence of the coastline changes from 1999 to 2019 in BHS were carried out. The model results showed that the amplitude of M2 tide increased slightly in Liaodong Bay and Bohai Bay, but decreased obviously in Laizhou Bay along with larger reclamation. The amplitude variation of the semi-diurnal constituents (M2, S2) was greater than the diurnal ones (K1, O1). The basin residence time in Liaodong Bay and Laizhou Bay increased by 5.44% and 49.44% from 1999 to 2019, respectively. Runoff of the Huanghe River can shorten the residence time of Laizhou bay while only having little effect on Bohai Bay and Liaodong Bay. The study of the Bohai Sea evolution can provide recommendations for subsequent marine ecological restoration efforts and serve as a reference for the study of other large semi-enclosed bays.